Self-Perceptions of Faculty of Sport Sciences Students on Demographic and Leadership Behaviors in the Fields of Management and Organization: A Critical Approach to Sports Feminism (Journal of Pharmaceutical Negative Results, 2022)
Human, time, space, material and physical item, use it in the most efficacious and rational style, the science of management based on collusive people for to some purpose, It is one of the popular notion used in the modern era. "Leadership self-perceiving", which should be evaluated within the discipline of "management science", which includes different methods, It is a versatile discipline in which law, political, economic and social aspects such as decision making, planning, organization, management, coordination and control are examined. It is a fact that there are gender-based criticisms in the fields of sports management and organization as a sub-system of the political systems that this discipline includes, and these criticisms focus on "women" in the context of sports feminism. In this context, it is aimed to determine the self-perceptions of the students of the faculty of sports sciences about the leadership behaviors of the female students who are directed to these fields by passing through a demographic analysis filter, to determine the leadership theories, the position of women in management and organizations in the context of sports feminism, and to trace the gender-based structure. In line with this purpose, it is a study in which undergraduate students of the faculty of sports sciences can evaluate their own self-leadership behaviors. This study was applied to 118 people studying in sports sciences. With the Self-Perceptions of Undergraduate Students' Leadership Behaviors Scale, which consists of four dimensions and twenty items, and the demographic form, the students evaluated their own leadership capacities.